2016
DOI: 10.31768/2312-8852.2016.38(3):191-194
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ω-FATTY ACIDS ON mRNA EXPRESSION LEVEL OF PPARγ IN PATIENTS WITH GASTRIC ADENOCARCINOMA

Abstract: Background: The antineoplastic role of peroxisome proliferator-activated receptor gamma (PPARγ) ligandshas previously been demonstrated in several gastric cancer cell lines. Activation of PPARγ by polyunsaturated fatty acids (PUFAs) inhibits growth and proliferationof tumor cells. In this double-blind clinical study, we evaluate the effect of PUFAs on PPARγ mRNA expression in patients with gastric adenocarcinoma. Materials and Methods: A total of 34 chemotherapy-naive patients diagnosed with gastric adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…In order to better understand the functions of DEGs in gastric cancer cells, GO and KEGG pathway enrichment analysis revealed that DEGs were mainly involved in intracellular signal transduction, energy metabolism, and fatty acid metabolism. This was consistent with the idea that the pathological process of gastric cancer was usually accompany with abnormalities in fatty acid metabolism [9,25]. Through computing the relevance of the constructed PPI network, 20 highly central genes were found to be the key nodes.…”
Section: Agingsupporting
confidence: 87%
See 1 more Smart Citation
“…In order to better understand the functions of DEGs in gastric cancer cells, GO and KEGG pathway enrichment analysis revealed that DEGs were mainly involved in intracellular signal transduction, energy metabolism, and fatty acid metabolism. This was consistent with the idea that the pathological process of gastric cancer was usually accompany with abnormalities in fatty acid metabolism [9,25]. Through computing the relevance of the constructed PPI network, 20 highly central genes were found to be the key nodes.…”
Section: Agingsupporting
confidence: 87%
“…Interestingly, studies have revealed that more lipid metabolism-related proteins, identified as oncogenes in eukaryotic cells, were highly expressed in many human cancers [6,7]. A high prevalence of gastric cancer was found in overweight individuals by epidemiological studies, and the significance of fatty acid metabolism in the development and progression of GC was increasingly recognized by scholars [8,9]. Moreover, lipids accumulation was also observed in the pathological tissues in GC [10].…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with the previous research that lipogenesis is important for various tumor cell growth. 35,36 The above data implied the molecular mechanism underlying lipid metabolism in GC.…”
Section: Discussionmentioning
confidence: 73%
“…O aumento da expressão do RNAm de TNF- em pacientes com neoplasia gástrica foi associado à presença do vírus H. pilory (Zabaglia et al, 2017;Hosseinzadeh et al, 2016 (Liu et al, 2008). Não houve diferença na expressão de RNAm de TNF-α em tecido neoplásico gástrico antes e após 3 semanas do emprego do quimioterápico cisplatina (Hosseinzadeh et al, 2016), assim como entre indivíduos que receberam ou não quimioterapia neoadjuvante para câncer gastroesofágico (Deans et al, 2006). O emprego das drogas 5-fluoracil e cisplatina associadas à radioterapia resultou em maior expressão de RNAm de TNF-α no sangue total de pacientes com tumor de esôfago (Bowen et al, 2015).…”
Section: Marcadores Inflamatóriosunclassified
“…Em estudo in vitro e in vivo demonstrou que a expressão do RNAm do PPAR-γ no tecido tumoral gástrico está associado com doença maligna em estágio menos avançado e com uma melhor sobrevida, sugerindo o uso do PPARγ como marcador de menor agressividade do carcinoma gástrico . Na literatura, a expressão de RNAm do PPAR-γ em tecido tumoral gástrico foi semelhante quando avaliado antes e após quimioterapia com cisplatina (Hosseinzadeh et al, 2016). No presente estudo, a expressão de RNAm da ZAG em sangue total foi semelhante entre todos os grupos de estudo, independente de apresentarem ou não neoplasia gástrica.…”
Section: Receptor Ativado Por Proliferador De Peroxissoma Gamaunclassified